Efficacy and Safety of Micropulse Transscleral Cyclophotocoagulation Use in Refractory Glaucoma Patients - Elsa Gustianty; Andika Prahasta; R. Maula Rifada; Ludwig Melino Tjokrovonco (Faculty of Medicine, Universitas Padjadjaran, 2022)
Glaucoma is the leading cause of irreversible blindness worldwide. Micropulse Transscleral Cyclophotocoagulation (MP-TSCPC) is a new method for treatment for refractory glaucoma with lesser complications than coventional TSCPC. This study aimed to evaluate the effectiveness and safety of MP-TSCPC (IRIDEX IQ810 Laser systems, CA) for refractory glaucoma treatment. This was a retrospective study using data obtained from the medical records of patients who underwent a MP-TSCPC procedure at Cicendo National Eye Hospital from July 2018 to September 2019. The outcomes measured were success rate (IOP decreased ≥30% from baseline with or without anti glaucoma medication at first month follow up) and post-operative complications. Fifty-seven eyes from 56 patients with a mean age of 57 years old underwent MP-TSCPC with 3 month follow up. The mean pre-operative intraocular pressure (IOP) dropped from 51.8 mmHg to 36.0 mmHg at 1 month follow up and 36.8 mmHg at the final follow up, representing an IOP decrease of 31% (1 month) and 28% (3 month). There was also a decrease of anti glaucoma medication usage from 2.51 to 2.16. The overall success rate at 1 month follow up was 49% and only 5% complication were found in this study. MP-TSCPC is safe and effective for lowering IOP and decreasing the need of anti glaucoma -medications in refractory glaucoma case. Further long-term evaluation and comparison to conventional TSCPC are still necessary.